2016
DOI: 10.12809/hkmj144499
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation genetic diagnosis for hereditary cancer syndrome: local experience

Abstract: A 33-year-old woman was referred for consideration of PGD because she was a BRCA2 gene mutation carrier. She had cancer of the right breast at the age of 24 years and underwent modified radical mastectomy with axillary dissection and immediate latissimus dorsi flap reconstruction. Adjuvant chemoradiotherapy was given and she was prescribed tamoxifen for 5 years after the operation. Her paternal grandmother had breast cancer diagnosed at the age of 60 years. Genetic screening was performed and confirmed the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The technique is applicable to hereditary diseases, such as thalassaemia and haemophilia, as well as hereditary cancer syndromes, including breast and colon cancers. 4 This is usually followed by confirmation by prenatal genetic testing after pregnancy.…”
Section: Genetic Testing and Counsellingmentioning
confidence: 99%
“…The technique is applicable to hereditary diseases, such as thalassaemia and haemophilia, as well as hereditary cancer syndromes, including breast and colon cancers. 4 This is usually followed by confirmation by prenatal genetic testing after pregnancy.…”
Section: Genetic Testing and Counsellingmentioning
confidence: 99%
“…found that only one in three couples agreed to use invasive PNT with the possibility of terminating the pregnancy. 22 Similarly, a study by Derks-Smeet et al. showed that the majority of couples with hereditary breast and ovarian cancer (HBOC) pathogenic variants refused to undergo PNT and even refused to follow natural conception.…”
Section: Hereditary Cancer Predisposition Genes and Diseasesmentioning
confidence: 99%
“… 13 HBOC Autosomal dominant BRCA2 ; BRCA1 gene pathogenic variant C.7436_7805del [GenBank U43746]); BRCA1 pathogenic variant carrier (5273G[A In exon 19) Breast cancer, ovarian cancer, pancreatic cancer, and prostate cancer Lee et al. 22 and Ramón et al. 27 FAP Autosomal dominant Truncating germline pathogenic variants in the APC gene APC gene, C.532-8G > A (NG_008481:G93262g > A); an AGTT deletion pathogenic variant in exon 15 of the APC gene FAP is hundreds or even thousands of polyps growing in the gastrointestinal tract, primarily in the colon Lee et al.…”
Section: Hereditary Cancer Predisposition Genes and Diseasesmentioning
confidence: 99%
See 2 more Smart Citations